1997
DOI: 10.1108/02602289710170311
|View full text |Cite
|
Sign up to set email alerts
|

Design of integrated systems for the control and detection of actuator/sensor faults

Abstract: Considers control systems operating under potentially faulty conditions. Discusses the problem of designing a single unit which not only handles the required control action but also identifies faults occurring in actuators and sensors. In common practice, units for control and for diagnosis are designed separately. Attempts to identify situations in which this is a reasonable approach and cases in which the design of each unit should take the other into consideration. Presents a complete characterization for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 21 publications
1
52
0
Order By: Relevance
“…However, some attention has been paid to the integrated design of the controller and the FDI filter (Jacobson & Nett, 1991, Stoustrup et al, 1997, Marcos & Balas, 2005, Castro et al, 2006. Stoustrup et al (1997) have shown that the optimal integrated design is equal to the optimal separate design of the controller and detection filter if there is no model uncertainty. When there is uncertainty the design is coupled and then an integrated approach would present a more advantageous framework for the trade-off between performance and robustness.…”
Section: Introductionmentioning
confidence: 99%
“…However, some attention has been paid to the integrated design of the controller and the FDI filter (Jacobson & Nett, 1991, Stoustrup et al, 1997, Marcos & Balas, 2005, Castro et al, 2006. Stoustrup et al (1997) have shown that the optimal integrated design is equal to the optimal separate design of the controller and detection filter if there is no model uncertainty. When there is uncertainty the design is coupled and then an integrated approach would present a more advantageous framework for the trade-off between performance and robustness.…”
Section: Introductionmentioning
confidence: 99%
“…In [304], it has been shown how a combined module for control and diagnosis can be designed, such that references are tracked, disturbances are robustly rejected, undetected faults do not have disastrous effects, the number of false alarms are reduced and the faults which have occurred are identified. Demonstrations of the applicability of this approach to valve fault accommodation on rocket engines, heat exchangers and autonomous underwater vehicles have been provided in [138], [21] and [153], respectively.…”
Section: Integrated Diagnostics and Control (Idc)mentioning
confidence: 99%
“…Most of the previous observer-based FD fault detection that have appeared in the literature although rather different compared to the one proposed in this paper, i.e. in [5], [6] an integrated approach was presented for fault tolerant control mainly via Youla parametrizations while addressed issues with uncertainty on the separation of the control and fault detection and raised a series of interesting issues.…”
Section: Introductionmentioning
confidence: 98%